PSIII-37 Dried Black Soldier Fly larvae as a dietary supplement to the diet of growing pigs. - Nekrasov, R (J Anim Sci, 2018)
Black soldier fly (Hermetia illucens) larvae are a promising source of nutrients for animal feeds. Dried Black Soldier Fly larvae (DBSFL) contains about 40% protein and fat. Recent data show that DLBSF also contains a significant amount of chitin, melanin, antimicrobial peptides, trace elements. Larva’s fat is rich in lauric and other medium-chain fatty acids. In the conditions subarctic climate of Russia LLC «NordTechSad» organized small-capacity production of BSF larvae. A new direction in the use of insect biomass is their use as a dietary additive to a pig diet. The aim of our research was to study the influence of small dosages of DLBSF on the growth and development crossbred pigs (N=18). The animals divided into 3 groups (n=6): 1 - a control group - standard feed (SF), 2 - experimental group (SF+0,3%BSF), and 3 - experimental group (SF+0,9%BSF). The materials obtained in the experiment was biometrically processed using the ANOVA method. The results of the study showed the use of DLBSF in feed increased average daily gain (ADG) of experimental animals during the growing period by 8.2 and 9.1% (424.80 ± 27.60 & 428.46 ± 26.94 vs. 392.68 ± 14.37 g, p>0.05) compared to the control group. Biochemical blood test showed a higher concentration of total protein (61.14 ± 1.40 & 57.57 ± 1.17 vs. 56.99 ± 0.53, g/L, p<0.05), decrease of bilirubin (8.65 ± 0.80 & 9.57 ± 1.33 vs. 13.98 ± 1.12, µmol/L, p<0.05), higher number of leukocytes (12.72 ± 0.53 &14.91 ± 0.52 vs. 8.80 ± 0.89, x 10(9)/L, p<0.05) in the blood of the experimental animals compared to the control group. Feeding animals with DLBSF did not affect the number of lactobacilli in the large intestine, while the number of bifid bacterias significantly increased to control group (3.0х10(14) & 1.4х10(12) vs. 1.0х10(11), CFU/g, p<0.05). Thus, it is possible to consider the prospects of using DLBSF as a dietary supplement to diets of rapidly growing pigs.